2D dynamic structure-soil-structure interaction for twin buildings in layered half-space II: Incident SV-waves. Issue 113 (October 2018) - Liang, Jianwen; Han, Bing; Todorovska, Maria I.; Trifunac, Mihailo D.
Abstract: A two-dimensional model for interaction through the soil of two identical vibrating structures, supported by rigid foundations embedded in a layered half-space, is presented for in-plane motions, and incident plane SV-wave. The formulation is based on the Indirect Boundary Element Method (IBEM). A similar model for incident SH-waves was presented in a companion paper. The formulation and results show higher level of coupling than for anti-plane motions. The vertical motions are coupled with the rocking and horizontal motions even for small motions, which is not the case for a stand-alone structure. At close distances, building relative response may be reduced by as much as 30% compared to the stand-alone structure, while otherwise it may be amplified, by as much as 50% for vertically incident SV-wave. For obliquely incident SV-wave, the building relative response of the illuminated structure may increase by 25%, while that of the structure behind would be reduced. Such phenomenon is consistent with earthquake observations in clusters of full-scale identical buildings. The effect of the other structure on the system frequency is small, within 3% for the cases considered. Highlights: IBEM formulation for in-plane 2D soil-structure-soil interaction (SSSI). Rigid foundations embedded in layered half-space; incident plane SV-wave. Characteristic frequencies of the problem derived based on Rayleigh scattering assumption. Coupling is more complex than for SH-wave case, occurring through all degrees-of-freedom. Up to 30% response reduction at close distances and 50% amplification possible.